2016
DOI: 10.1242/dev.129783
|View full text |Cite
|
Sign up to set email alerts
|

The LGN protein promotes planar proliferative divisions in the neocortex but apicobasal asymmetric terminal divisions in the retina

Abstract: Cell division orientation is crucial to control segregation of polarized fate determinants in the daughter cells to produce symmetric or asymmetric fate outcomes. Most studies in vertebrates have focused on the role of mitotic spindle orientation in proliferative asymmetric divisions and it remains unclear whether altering spindle orientation is required for the production of asymmetric fates in differentiative terminal divisions. Here, we show that the GoLoco motif protein LGN, which interacts with Gαi to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…However, in epidermis, we and others have shown that LGN forms an apical complex with Insc, Gαi3, NuMA, dynactin and Par3 and that LGN loss leads to loss of perpendicular divisions, impaired Notch signaling and lethal defects in epidermal barrier formation and differentiation (Lechler and Fuchs, 2005;Poulson and Lechler, 2010;Williams et al, 2011Williams et al, , 2014. Similar roles for LGN in promoting perpendicular/ asymmetric divisions have been reported in retina and mammary gland (Ballard et al, 2015;Chiu et al, 2016;Lacomme et al, 2016). The molecular mechanisms that regulate the differential subcellular localization of LGN in progenitors undergoing both symmetric and asymmetric cell divisions remain largely unknown.…”
Section: Discussionsupporting
confidence: 66%
“…However, in epidermis, we and others have shown that LGN forms an apical complex with Insc, Gαi3, NuMA, dynactin and Par3 and that LGN loss leads to loss of perpendicular divisions, impaired Notch signaling and lethal defects in epidermal barrier formation and differentiation (Lechler and Fuchs, 2005;Poulson and Lechler, 2010;Williams et al, 2011Williams et al, , 2014. Similar roles for LGN in promoting perpendicular/ asymmetric divisions have been reported in retina and mammary gland (Ballard et al, 2015;Chiu et al, 2016;Lacomme et al, 2016). The molecular mechanisms that regulate the differential subcellular localization of LGN in progenitors undergoing both symmetric and asymmetric cell divisions remain largely unknown.…”
Section: Discussionsupporting
confidence: 66%
“…There is growing evidence that LGN and other intrinsic polarity protein members can regulate cellular asymmetry in a range of mitotic and non‐mitotic cells, including endothelial cells , retinal progenitor cells or glutamatergic neurons . Thus, it will be interesting to investigate if compromised proteostasis also interferes with polarity in these structures.…”
Section: Discussionmentioning
confidence: 99%
“…Work on mouse skin shows that the polarity regulators aPKC and Par3, together with Insc and the vertebrate homolog of Pins, LGN (also known as GPSM3), set the balance for symmetric and asymmetric stem cell divisions (Lechler and Fuchs, 2005;Poulson and Lechler, 2010). Recent evidence from retinal progenitors suggests similar mechanisms of polarity-and LGN-assisted asymmetric divisions during eye development (Lacomme et al, 2016).…”
Section: Asymmetric Stem Cell Divisionmentioning
confidence: 99%